The Effect of Nutrition Counseling on Nutrition Intake and Weight Growth for Children Aged Less than Five Years in Tombo-Tombolo Village, Bangkala District, Jeneponto District - Nurlina Nurlina; Wibowo Wibowo (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2019)
The intake of nutrients a child obtained through daily consumption of food plays a major role in the child's life. The parameters to measure the progress of usable growth were weight. If the children were measured weight periodically, the picture or pattern was gotten of growth of the child. This study aimed to determine the effect of nutritional counseling on nutrient intake and weight growth of children under five in the village Tombo-tombolo district Bangkala Jeneponto district. Counseling was done 3 times 30 minutes a month. This study was a pre-experimental study with one group pretest-posttest design. Samples are 33 children, that was children aged 6 - 24 months were chosen purposively. The data of nutrient intake was obtained through the method of an interview using the 24-hour recall method for 2 days, body weight data obtained by weight measurement by comparing growth patterns in KMS. The data were analyzed using the McNemar test using SPSS program. Mc Nemar test results were indicated that there was influenced nutrition counseling on energy intake, p-value = 0.03. There was no effect of nutritional counseling on protein intake, p-value = 0.25. There was the influence of nutrition counseling to fat intake, value p = 0.03. There was an influence of nutrition counseling to growth weight of children under five, value p = 0.01. Keywords: Counseling nutrition, Energy, Protein, Fat, Weight